The importance of structure in the teaching of mathematics with special reference to multiplication - Medford, R.
A pictorial test was administered to pupils of the 7-8 age range, to see whether they could read and write a numeral and identify the units and "tens" places in it. This was followed by a course of five lessons, emphasizing place value of the numeration system and the distributive property of multiplication. Results of the achievement test suggest four principles to be observed when teaching mathematics
Focus on the Classroom. Research Notes by Practising Teachers
Keywords: Primary school mathematics